Effects of acute hypothyroidism on plasma melatonin and Aanat and Asmt expression in the pineal gland and gonads of rats - Paiva, Rafaella Valete Nunes; Mondes, Pedro Henrique de Lima; Brandão, Beatriz de Jesus; Sant’Anna, Julia Nascimento; Freire dos Santos, Maria Eduarda; Fighera, Yasmin Muniz; Santos, Luciano Cardoso; Markus, Regina P.; Fernandes, Pedro Augusto Carlos Magno; Silva, Juneo Freitas; Tamura, Eduardo Koji (Frontiers in Endocrinology, 2024)
The reproductive system is tightly regulated by environmental and physiological signals. Melatonin, known as the hormone of darkness, plays a crucial role in regulating both the circadian and reproductive systems in mammals. Hypothyroidism is a key endocrine disorder that harms the reproductive system. Despite many studies on melatonin's effects on the reproductive system, there is conflicting information regarding melatonin synthesis modulation in hypothyroidism. The objective of this study was to investigate the modulation of plasma melatonin levels and gene expression of Aanat and Asmt in the pineal gland and gonads of rats with hypothyroidism at different times of the day. Female and male Wistar rats were divided into control and hypothyroid groups. Hypothyroidism was induced using propylthiouracil (PTU; 15 days), rats were euthanized 6h after lights on (ZT6), before lights off (ZT11.5), and 6h after lights off (ZT18). Free thyroxine (FT4) and melatonin were quantified in plasma, and gene expressions of melatonin synthesizing enzymes (Aanat and Asmt) were measured in pineal and sexual organs (testis and ovary). Also, morphological analysis was performed in sexual organs. The results reveal some disparities between the sexes. Hypothyroidism reduced antral and primary follicles in the ovary, and reduced the weight of testis, epididymis, and prostate. In relation to gene expression, we observed a reduction in Aanat expression in the pineal gland during the light phase (ZT6), and in males, this reduction occurred during the dark phase (ZT18). Regarding Asmt expression, there was a decrease in females also during the dark phase (ZT18). In the gonads, there was an increase in expression in both sexes at ZT11.5. Additionally, it was interesting to observe the association between FT4 levels and Asmt expression in the gonads. This study showed that acute hypothyroidism can affect components of the melatonergic system in gonads, particularly gene expression of melatonin synthesis enzymes (Aanat and Asmt) contributing to changes in reproduction organs during disease progression. These findings enhance our understanding of melatonin synthesis in the reproductive system during hypothyroidism, showing distinct responses in male and female rats, and suggest that hypothyroidism affects the circadian rhythmicity of melatonin synthesis in a sex-dependent manner.